Optimization of Dominant Strain Composite Fermentation for Jianqu and Dynamic Changes in Amylase Activity - Xie, Ruilin; Zhang, Zhi; Jian, Xiaohong; Li, Zaixin (International Journal of Public Health and Medical Research, 2025)
To ensure the safe production of Jianqu, the dominant strains —Absidia corymbifera, Lichtheimia ramosa, and Mucor circinelloides—identified through high-throughput sequencing analysis, were inoculated onto sterile Jianqu-building substrates for cultivation. Their appearance characteristics were observed, and the liquefying and saccharifying power of their amylase were measured. Subsequently, Saccharomycopsis fibuligera, Millerozyma farinose, Hyphopichia burtonii, Absidia corymbifera, Lichtheimia ramosa, Mucor circinelloides, and Monascus purpureus were co-inoculated onto Jianqu-building substrates in different proportions for composite fermentation. The fermentation phenomena were observed, and the liquefying and saccharifying power of amylase were detected to further evaluate the effects of restricted composite fermentation using different proportions of dominant strains. The results showed that when the ratio of yeast (Saccharomycopsis fibuligera, Millerozyma farinose, Hyphopichia burtonii were mixed in a ratio of 2: 1: 1): Absidia corymbifera :Lichtheimia ramosa :Mucor circinelloides :Monascus purpureus was 2:4:3:2:1, the fermentation product achieved the ideal state of "ubiquitous white mold with a fragrant alcoholic aroma." The changes in amylase liquefying and saccharifying power exhibited an "S"-shaped curve. At 84 hours of fermentation, the liquefying power reached 2.11 ± 0.08U, and the saccharifying power reached 398 ± 5U, significantly outperforming natural fermentation (P < 0.05). Conclusion: By adjusting the inoculation ratios of dominant strains, the liquefying and saccharifying power of amylase can be significantly enhanced, thereby shortening fermentation time and improving the quality of Jianqu fermentation.